The Novel Application of Genomic Profiling Assays to Shorten Inactive Status for Potential Kidney Transplant Recipients With Breast Cancer. Issue 1 (7th September 2016) - Mukhtar, R. A.; Piper, M. L.; Freise, C.; Van't Veer, L. J.; Baehner, F. L.; Esserman, L. J.
Abstract : The concern about cancer recurrence has traditionally resulted in delaying kidney transplantation for 2–5 years after a cancer diagnosis in patients who are otherwise eligible for transplant. This period of inactive status to observe the tumor biology can result in significant morbidity and decreased quality of life for patients with end‐stage renal disease (ESRD). We reported the novel application of genomic profiling assays in breast cancer to identify low‐risk cancers in two patients with ESRD who were able to have the mandatory inactive status eliminated prior to kidney transplantation. Abstract : In a novel approach to stratify risk of recurrence in two patients diagnosed with breast cancer during the pretransplantation evaluation period, tumor genomic profiling, via commercially available tests, demonstrating low risk of recurrence enables a decision to proceed with kidney transplant without the typical waiting period, with excellent results.